Multiculturalidade e educação para a cidadania : o começo de uma história, ou há ciganos em Alcobaça - Antunes, Adelino J., 1950- (1998)
Intervenção social. - ISSN 0874-1611. - N. 17-18 (1998). - p. 85-109